Модифікування магнетиту діоксидом титану та властивості одержаних нанокомпозитів - Семко, Л.С.; Горбик, П.П.; Чуйко, О.О.; Сторожук, Л.П.; Дубровін, І.В.; Оранська, О.І.; Рево, С.Л. (Видавничий дім "Академперіодика" НАН України, 2007)
A technique of obtaining the nanocomposites on the basis of magnetite modified by titanium dioxide is worked out. The TiO2 content varied from 0.1 to 0.5 g per 1 g of the magnetite. N-butylorthotitanate was used as a modifying agent. The structure and magnetic properties of the obtained nanocomposites are investigated.